Changes in amplitude characteristics of heart sound signals during external-cuff-inflation procedure: A pilot study - Xinpei Wang; Yuanyang Li; Chengyu Liu; Changchun Liu; Lizhen Ji; Haibin Zeng (Computing in cardiology, 2016)
Changes in amplitude characteristics of the first heart sound (S1) and second heart sound (S2) have been confirmed to be linked with the physiological or pathological changes of cardiovascular system. Earlier studies have also documented that these changes in amplitudes of S1 and S2 were correlated with blood pressure (BP) factor. External-cuff-inflation-deflation (ECID) is a standard procedure for BP measurement, and will certainly influence the BP state in the arterial trees. However, no existing studies report whether this ECID procedure will change the amplitude characteristics of S1 and S2. This study aimed to provide insight into this information. Thirty-one healthy volunteers were enrolled. Heart sound and cuff pressure signals were recorded synchronously for each subject during a resting state and then followed by a external-cuff-inflation (ECI) state and a external-cuff-deflation (ECD) state. The BP measurements included two patterns: cuff wrapped on the left upper arm and cuff wrapped on the two-side arms and legs. The amplitudes of S1 (S1_amp) and S2 (S2_amp), as well as their ratio (S1/S2), were calculated for each beat signals and then were averaged for each state. These three indices were compared between resting and ECI states, also between resting and ECD states using paired-t test. The results showed that S2_amp had significant differences between resting and ECI states with cuffs on the two-side arms and legs (p<;0.01). To conclude, this pilot study suggested that the applied ECI procedure with cuffs on the two-side arms and legs during BP measurement significantly influences the amplitude characteristics of S2.